The Greenspan Era: Discretion, Rather than Rules - Friedman, Benjamin M (American Economic Review, 2006)
What stands out in retrospect about U.S. monetary policy during the Greenspan Era is the ongoing movement away from mechanistic restrictions on the conduct of policy, together with a willingness on occasion to depart even from what more flexible guidelines dictated by contemporary conventional wisdom would imply, in the interest of carrying out the Federal Reserve System's dual mandate to pursue both stable prices and maximum employment. Part of this change was procedural -for example, the elimination of money growth targets. The most substantive demonstration of policy flexibility came in the latter half of the 1990s, as unemployment fell below 6% (in 1994), then below 5% (in 1997), and then remained below 5% for more than four years, yet the Federal Reserve did not tighten monetary policy. This policy stance was consistent with a view of the economy, including faster productivity growth and increased exposure to international competition, that Chairman Greenspan had articulated nearly a decade before.